Effect Of Ageing Treatment On Force-Deflection Behaviour Of NiTi Wire In Three-Point And Three-Bracket System - Shamsul Khair, Nurul Syifa’ (Universiti Sains Malaysia, 2022)
NiTi archwires used for levelling and alignment of the teeth are required to have a good operating range that can provide light and constant force applied to the teeth. During the teeth levelling phase of orthodontic treatment, a rectangular superelastic NiTi archwire is usually used due to its ability to transmit torque and align the position of tooth. However, rectangular archwire can only be applied after round wire has levelled the teeth to a certain extent. This is due to the high stiffness and high torque that is produced by rectangular wire. This study was designed to investigate the effect of ageing treatment on the force-deflection behaviour of superelastic NiTi wire bent in three-point and different interbracket settings. In this case, three-point bending was first conducted to measure the bending deformation of 0.016 × 0.022-inch of rectangular superelastic NiTi archwires bent after being aged at various temperatures with different durations. Subsequently, bending in a three-bracket system was performed using aged wires with the lowest unloading force for each ageing duration, which were selected based on the data from three-point bending test. Findings of the study revealed that the bending force generated by the NiTi archwire during the unloading cycle was effectively lowered by the ageing treatment. The plateau slope, which depicts the force constancy of the wire, considerably differed between as-received and aged wires. During three-point bending, ageing setting of 490 °C at 45 minutes exerted the lowest unloading forces (1.72 N) whereas as-received wire produced 2.99 N. In the three-bracket system, the least force magnitude was yielded by wires aged at 490 C for 45 minutes with 11 to 33% force reduction as compared to as-received wires. Ageing parameter with the best constant force delivery in three-bracket bending is produced at 460 C for 35 minutes. It was also observed that flat force plateaus were produced during the unloading when archwires were employed in wide interbracket distance, which are 8.5 and 9.0 mm. The ageing treatment approach may be utilised to further adjust the superelastic NiTi arch wire's deformation behaviour so that it will exert the appropriate amount of force during tooth levelling treatment.